Pengelolaan lahan dan ruang hutan dengan perspektif kearifan lokal komunitas Ammatoa Kajang sebagai usaha konservatif - Muhammad Syainal Nur; Muhammad Zid; Cahyadi Setiawan (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2022)
Land and space management has become a big concept and agenda to answer two major problems that are currently happening, first, the availability of land and space for development which is dwindling, second, forest conservation due to the damage that has occurred due to the development. The Ammatoa Kajang community is a community that owns and chooses to maintain local wisdom called Pasang Ri Kajang, a value system that focuses on environmental conservation. This research is descriptive qualitative using the literature method with a research focus on land and forest space management issues with the perspective of local wisdom of the Ammatoa Kajang community as a conservative effort. Researchers collect and utilize various secondary information through related journals and articles. The results showed that with Pasang Ri Kajang which is believed to be a noble value, the Ammatoa Kajang indigenous people have a high concern for forests and the environment, thus providing a positive impact on forest conservation. In several other areas that have and choose to maintain local wisdom in the social system of their indigenous peoples, it is known to have the same positive impact, both from an ecological and economic perspective.